O możliwości uznania prawa do sprzeciwu sumienia w obszarze podatków - Łukaszewicz, Adam (Kwartalnik Prawa Publicznego, 2014)
The objective of the paper is to explore the possibilities of the recognition of the conscientious objection to taxes as a protectable manifestation of the right to freedom of conscience and religion as enshrined in modern constitutions and international treaties on the protection of human rights. The author, in contrast to mainstream Polish legal doctrine, espouses the wide approach to the right to freedom of conscience which should be construed as a general right to lead one’s life in conformity with internalised moral precepts. In consequence, the freedom of conscience encompasses inter alia the right not to be coerced into action that would amount to a grave detriment to one’s moral integrity and identity, which is tantamount to the inclusion of the general right to conscientious objection regardless of its recognition in a statute. Nevertheless, a particular modality of the conscientious objection cannot enjoy constitutional protection, unless it is compatible with other constitutional principles and values. As conscientious objectors to taxes indirectly attempt to influence the decisions on state expenses adopted by the Parliament, this form of objection is irreconcilable with the principle of representative democracy, constitutional assignation of the budgetary powers to the government and parliament, and the constitutional tasks attributed to the Armed Forces .